2019
DOI: 10.1155/2019/7358710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3D Nonlinear Earthquake Behaviour of the Ilısu CFR Dam under Far‐Fault Ground Motions

Abstract: In the recent times, many huge concrete face rockfill dams (CFRDs) have been modelled and constructed in the world, and many of these dams are located on the strong earthquake zones. Examination of the seismic behaviour of a CFR dam built on the seismic zone is very important to assess the safety and future of the dam. For this reason, the nonlinear earthquake behaviour of these dams should be constantly observed taking into account the seismicity of the zone. In this study, three-dimensional (3D) seismic beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…On the other hand, to ensure the channel's proper operation, its associated hydraulic and hydromechanical installations, including gates and valves, the flow discharge capacity should be carefully examined along with performing hydraulic model tests [2]. By studying failure causes of dams' terminal gates, it has been determined that the cavitation phenomenon and gate vibration are the chief reasons for damages, because, in the areas where air bubbles collapse, pressure fluctuations intensity raises [3][4][5][6][7][8]. At the bottom outlets, the two-phase air-water flow is transmitted at high speed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to ensure the channel's proper operation, its associated hydraulic and hydromechanical installations, including gates and valves, the flow discharge capacity should be carefully examined along with performing hydraulic model tests [2]. By studying failure causes of dams' terminal gates, it has been determined that the cavitation phenomenon and gate vibration are the chief reasons for damages, because, in the areas where air bubbles collapse, pressure fluctuations intensity raises [3][4][5][6][7][8]. At the bottom outlets, the two-phase air-water flow is transmitted at high speed.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [17] studied the influence of valley topography on the deformation and stress of a high concrete face rockfill dam and found that the stress and deformation gradient of the face slab increased exponentially when the valley widthheight ratio was less than 2. Karalar and Çavus ¸li [18,19] used a WIPP-creep viscoplastic material model and a burgercreep viscoplastic material model to represent the concrete slab, rockfill materials, and foundation of a concrete face rockfill dam within an investigation of the deformation of the Ilısu Dam in Turkey. Gao et al [20] examined monitoring data for 22 concrete face rockfill dams across eight countries and found a low correlation between valley factors and deformation of the face slab below a certain valley factor threshold, whereas abrupt changes to the slope angle aggravated deformation of the slab.…”
Section: Introductionmentioning
confidence: 99%
“…Finite Element Method (FEM) has demonstrated advantages for predicting the mechanical performance of dams for better management and maintenance [20][21][22][23][24][25][26][27]. e FEM can also provide useful guidance for the design and construction of new high CFRDs by optimizing dam body structures, construction procedures, and dam construction materials [8].…”
Section: Introductionmentioning
confidence: 99%